Insulin Resistance in Non Diabetic Chronic Hepatitis C patients - Zaghlol, Mohamed; Al-Sayed, Mohamed; Mohamed, Ahmed Qasem; Mustafa, Hamdy Mahfouz; Omar, Heba (Journal of medical and pharmaceutical sciences, 2017)
Patients with chronic hepatitis have impaired glucose metabolism with hyperinsulinemia and insulin resistance, this hyperinsulinemia has been shown to be due to decreased insulin catabolism rather than increased pancreatic insulin secretion.We aim to evaluate insulin resistance in non diabetic patients with chronic hepatitis C virus infection. our study was a case-control study conducted in Tropical Medicine and Gastroenterology Department AL-Azhar University Hospital. 60 patients and 30 healthy controls were included in the study. The patients were classified into two groups:Group A: 30 patients with chronic hepatitis C infection were selected with positive HCV RNA in serum for at least 6 months; Patients were not receiving anti-viral therapy at the time of sampling They showed no evidence of cirrhosis. Group B: 30 patients with HCV related liver cirrhosis. They were divided according to Child Pugh score; twenty patients with HCV related compensated liver cirrhosis (Child A) Ten patients with HCV related decompensated liver cirrhosis (Child B and C). Group C: The control group: included 30 healthy individuals.  All patients and control were subjected to the following: Liver function tests: Alanine transaminase (ALT), Aspartate transaminase (AST), total and direct bilirubin, total protein, serum albumin. Prothrombin time (PT) & international normalization ratio (INR). Renal function tests: Blood urea nitrogen (BUN), Na, K. Complete blood count. Alpha fetoprotein (αFP).  Overnight fasting and two hours postprandial blood glucose level. Fasting serum insulin of each individual.  Insulin resistance was  determined via the Homeostasis  Model assessment (HOMA-IR)Statistical analysis of data will be done by using SPSS(statistical program for social science version22,produced by IBM SPSS Inc.,Chicago,USA).Results: We found that out of 30 CHC and 30 LC (20 compensated LC, 10 de compensated LC) 8 (26.7%); 8 (40%) patients and 5(50%) respectively had HOMA-IR levels greater than 2.5, which is consistent with IR diagnosis. Decompensated cirrhotic patients showed higher frequency of IR compared  to CHC, and compensated cirrhotic patients.Coclusion: In chronic hepatitis C patients, HOMA-IR, fasting serum insulin and fasting blood glucose were significantly higher than healthy controls.
Keywords: Insulin resistance; chronic hepatitis C